Pengaruh Media Interaktif Kahoot! terhadap Hasil Belajar Teks Editorial Siswa Kelas XII SMAN 1 Pangkep - Marizka, Marizka; Usman, Usman; Wijayanti, Tuti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to determine the Interactive Media Kahoot! Against Editorial Text Learning Outcomes of XII UPT Class Students of SMAN 1 Pangkep Pangkep Regency. The independent variable in this study is kahoot! interactive media and the dependent variable is the learning outcomes of students on editorial text material. The population in this study were all students of class XII UPT SMAN 1 Pangkep consisting of 11 classes, the samples were class XII Amanah and XII Energik with 25 students each. The data of the research were obtained by giving the posttest of editorial text learning outcomes test. The data analysis technique is descriptive statistical analysis using IBM SPSS Statistic application. Based on the results of the posttest, it was found that the average test score of students' learning outcomes using Google Form was 54.8 and the average test score of students' learning outcomes using interactive media kahoot! was 74. The results of the study based on the statistical analysis of the t test obtained the comparison value of the t value and t table is 5.985> 2.012. Thus it can be concluded that kahoot! interactive media has a significant effect on the learning outcomes of editorial text students of class XII UPT SMAN 1 Pangkep Pangkep Regency.